A Randomized Double‐Blind Controlled Trial of Intravenous Meloxicam in the Treatment of Pain Following Dental Impaction Surgery. (12th January 2018) - Christensen, Steven E.; Cooper, Stephen A.; Mack, Randall J.; McCallum, Stewart W.; Du, Wei; Freyer, Alex
Abstract: This randomized, controlled phase 2 study was conducted to evaluate the analgesic efficacy, safety, and tolerability of single intravenous (IV) doses of 15 mg, 30 mg, and 60 mg meloxicam compared with oral ibuprofen 400 mg and placebo after dental impaction surgery. The primary efficacy end point was the sum of time‐weighted pain intensity differences for 0‐24 hours postdose. Among 230 evaluable subjects, meloxicam IV 60 mg produced the greatest reduction in pain, followed by the 30‐mg and 15‐mg doses. Statistically significant differences in summed pain intensity differences over 24 hours were demonstrated for each active‐treatment group vs placebo (favoring active treatment) and for meloxicam IV 30 mg and 60 mg vs ibuprofen 400 mg (favoring meloxicam IV). Moreover, there was a statistically significant dose response for meloxicam IV 15 mg to 60 mg. The onset of action for meloxicam IV was rapid and sustained; significant differences in pain intensity differences were detected as early as 10 minutes postdose and lasted through the 24‐hour postdose period. Subjects in the meloxicam IV groups were more likely than placebo recipients to achieve perceptible and meaningful pain relief and were less likely to use rescue medication. Patient‐reported global evaluation showed that meloxicam IV 60 mg had the highest rating. There were no deaths, serious adverse events, or discontinuations due to adverse events. The incidence of subjects with ≥1 treatment‐emergent adverse event was greatest in the placebo group, followed by the groups that received ibuprofen, meloxicam IV 15 mg, 30 mg, and 60 mg. Nausea was the most commonly reported treatment‐emergent adverse event. Clinical trial registration number: NCT00945763.